Bridging Minds And Hearts: A Human - Centric Shift From Pedagogy To Andragogy In First- And Second-Year Undergraduates At The Faculty Of Law - Udayanganie, U.A.T. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and Surana International Attorneys India, 2025)
Law serves as a fundamental structure in society, aiming to ensure security, freedom, and dignity. Therefore, law is not an independent entity existing apart from society; rather, it is deeply interwoven with the fabric of social life. Law students must be adequately equipped to sensitize towards social realities. While traditional methods and modules of teaching law effectively contribute to the enhancement of knowledge, they have proven inadequate in addressing the development of essential skills, attitudes, and mindsets. In response, the Faculty of Law revised its curriculum, adopting a human-centric approach to legal education by introducing innovative course modules. This paper focuses on introducing two new subjects, Law and Society and Aesthetic Appreciation of Law, which represent this transformative shift. These courses bridge theoretical knowledge with practical and societal relevance, emphasizing critical thinking, empathy, and a holistic understanding of the law. This paper centers on two key questions: how can andragogical principles be integrated into the legal curriculum for first- and second-year students, and how do innovative course modules contribute to developing essential skills like critical thinking and empathy? This paper aims to evaluate the effectiveness of new course modules, such as Law and Society and Aesthetic Appreciation of Law, in achieving human-centric legal education emphasizing the importance of empathy, ethics, and societal engagement in shaping future legal professionals. This study argues that the transition from traditional pedagogy to andragogy in teaching first- and second-year law undergraduates can enhance student engagement, promote social responsibility, and foster equity by sensitizing students to the impacts of laws on individuals and communities. The argument is grounded in the belief that andragogy is essential for adopting a human-centric approach to teaching law as it emphasizes learner autonomy, experiential engagement, and the development of critical thinking and empathy, aligning education with the cognitive and emotional needs of adult learners. This research employs a qualitative case study approach, drawing upon three key theoretical foundations: Malcolm Knowles' Andragogy, Lev Vygotsky's Constructivist Theory, and Carl Rogers' Person-Centered Approach.
Keywords: Human centric approach; Pedagogy; Andragogy; Legal education; Experiential learning